(untitled) (Journal of Medical & Health Sciences Review, 2025)
The paper focuses on exploring how ethical leadership influences job stress and counterproductive work behavior (CWB) among the health care professionals in the private hospitals within the city of Hyderabad in Pakistan. Data collection was done by using the Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA) on 400 respondents (200 doctors and 200 nurses). The results indicate that ethical leadership has a great impact on decreasing both job stress and CWB, whereas job stress positively forecasts CWB. Also, job stress mediates the association between ethical leadership and CWB, and it is imperative to reduce stress as a route towards negative employee behaviors minimization. The MGA does not show any significant differences between doctors and nurses, as to suggest that ethical leadership works equally across the two groups. These findings demonstrate the importance of ethical leadership in determining the employee well-being and behavioral outcomes within the healthcare setting. The research has practical suggestions that hospital administrators may use to enhance the quality of leadership, minimize stress, and promote positive organizational behavior. These are cross-sectional design and restriction to the private hospitals in a single city. Further studies are needed in the longitudinal impact and extensive institutional and geographical comparison.